Pertumbuhan ikan kuwe putih Caranx sexfasciatus di karamba jaring apung yang diberi pakan rucah dengan bahan tambahan yang berbeda - Mansauda, Grace F; Sampekalo, Julius; Lumenta, Cyska (e-Journal BUDIDAYA PERAIRAN, 2013)
The use of trash fish ( Treatment A ), trash fish + cassava( Treatment B), pellets+ trash fish ( Treatment C ) and a mixture of trash fish + cassava + pellets ( Treatment D ) as feed had been conducted to evaluate its effect on growth of Caranx sexfasciatus. This research was carried out inTelengen Bay waters, Central Tabukan District, Sangihe Islands Regency. Fish with weighing 60,9 -62,9 g were distributed in 12 net cages measuring 3x1x1 m with the density of 5 fish each. Fish were fed three times a day for seven weeks. Fish weight was measured every week. At the end of experiment, the individual weight of fish ranged from 168,7 to 222,8 g in with the highest average weigth gain was achieved in treatment A namely 222.8 g (354.2%)), followed by treatment C 178.0 g (286.6 %) treatment D 170.08 g (280.5%), and treatment B as much as 168.7 g (274.3%). Statistical analysis displayed that weight gain of fish in treatment A was significantly different as compared to that of treatments B, C, and D. There was no significant differencesbetween treatment B, C, and D. Food conversion ratio of treatment A was significantly different compared to other treatments. Food conversion ratio of treatment A was 2.80, B 4.25, C 3.70, D 3.88. as conclusion, the use of trash fish without supplementaion with others ingradients resulted in the highest absolute and relatif growth of fish and the lowest food conversion ratio of 2.80 as compared to other treatments. Keywords: Caranx sexfasciatus, weight gain, food conversion ratio, floting net cage